The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1101/2023.04.21.537845
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Human Breast Cell Atlas Mapping the Homeostatic Cellular Shifts in the Adult Breast

Abstract: One of the barriers for breast cancer prevention and treatment is our poor understanding of the dynamic cellular shifts that naturally occur within the breast and how these changes contribute to tumour initiation. In this study we report the use of single cell RNA sequencing (scRNAseq) to compile a Human Breast Cell Atlas (HBCA) assembled from 55 donors that had undergone reduction mammoplasties or risk reduction mammoplasties. The data from more than 800,000 cells identified 41 cell subclusters distributed ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…Epithelial cell types were annotated using CD49f/EpCAM markers as done previously into mature luminal (ML), luminal progenitors (LP) and basal cells 11 . These cell clusters have been described with various names in the literature 7,8,12 . In a recent breast cell annotation event organized by Chan-Zuckerberg Initiative that included several research groups involved in developing single cell atlas of the breast, the following terminologies were suggested: luminal hormone sensing (LHS), luminal adaptive secretory precursor cells (LASP) and basal-myoepithelial (BM) cells for mature luminal, luminal progenitor, and basal cells, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Epithelial cell types were annotated using CD49f/EpCAM markers as done previously into mature luminal (ML), luminal progenitors (LP) and basal cells 11 . These cell clusters have been described with various names in the literature 7,8,12 . In a recent breast cell annotation event organized by Chan-Zuckerberg Initiative that included several research groups involved in developing single cell atlas of the breast, the following terminologies were suggested: luminal hormone sensing (LHS), luminal adaptive secretory precursor cells (LASP) and basal-myoepithelial (BM) cells for mature luminal, luminal progenitor, and basal cells, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Murrow et al characterized premenopausal breast tissue at the single cell level to determine coordinated transcriptional programs that alter in response to changing hormonal levels 9 . Two other single cell studies using reduction mammoplasty samples identified three major epithelial cell types in the breast 10,12 . However, there remains a lack of information in differences in cell state based on genetic ancestry and relationship between cell state as defined by transcriptome and chromatin accessibility status.…”
Section: Introductionmentioning
confidence: 96%
“…2A). This held true on datasets from diverse organ systems and origins: Human Lung Cell Atlas (2.3 million cells [18]), the 1 million cell survey of embryonic development from Cao et al [19], the Human Breast Cell Atlas (800,000 cells [20]), and the DCM/ACM Heart Cell Atlas (881,000 cells [21]).…”
Section: Resultsmentioning
confidence: 99%
“…The breast biology field has invested greatly in dissecting human breast heterogeneity with over 1 million single cells across 200 human breast tissues profiled by scRNAseq to date 2,4,7,8,32 .…”
Section: Discussionmentioning
confidence: 99%